Retinal Optical Coherence Tomography Angiography Parameters Between Patients With Different Causes of Chronic Kidney Disease - Yong, Meng Hsien; Ong, Ming Yean; Tan, Kuan Sze; Hussein, Siti Husna; Mohd Zain, Ayesha; Mohd, Rozita; Mustafar, Ruslinda; Wan Abdul Halim, Wan Haslina (Frontiers in Cellular Neuroscience, 2022)
Background: CKD is a major public health issue because of the rising number of patients with risk of progression to end stage renal disease. The retinal micro-vasculatures provide an unique window to assess on the systemic microcirculation. OCTA parameters may provide a non-invasive method for the systemic correlation. This research aims to compare the association of OCTA parameters in different causes of CKD. Methods: This is a single centre cross-sectional study on CKD patients at Universiti Kebangsaan Malaysia Medical Centre over 2 years. CKD patients were divided into three groups: DM group (diabetic CKD), HPT group (hypertensive CKD), AG group (autoimmune-related glomerulonephritis CKD). OCTA parameters namely, foveal avascular zone (FAZ), vascular density (VD), perfusion density (PD) and macular volume (MV) were measured and recorded using OCTA. Blood and urine analyses were taken as patient’s CKD profile. The demographic data, OCTA parameters and CKD profiles were analysed using SPSS version 23. Results: The right eyes of 232 patients were included. The median age of control and CKD subjects were 36 and 61 years old respectively. The proportion of subjects under control, DM, HPT, and AG group were 30.6%, 53.4%, 5.6%, and 10.4% respectively. There was no significant difference in FAZ, but significant difference in VD, PD, MV between control group and CKD group. There was statistically significant different in between the 3 different causes of CKD in VD and PD (p<0.001, p=0.001, respectively). When compared with control group for VD and PD, there were significant difference between DM-control group (p<0.001, p<0.001) even when the age variable was considered, but no significant difference when comparing HPT-control and AG-control. There was significant correlation between age, FBS, HbA1c with VD and PD. There was no significant association between CKD profile and FAZ. Conclusion: Our study showed the meaningful reduction of VD and PD in diabetic CKD patients. However, the use of OCTA to screen or predict CKD in patients living with diabetes mellitus, hypertension or autoimmune nephritis was not shown to be useful.